PERAN PEMASARAN SYARIAH SEBAGAI UPAYA PENINGKATAN DAYA SAING UMKM DI KABUPATEN ROKAN HILIR - Arpizal Arpizal; Rokiyah Rokiyah; Usnan Usnan (TAKAFUL: Jurnal Ekonomi Dan Perbankan Syariah, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in improving the community's economy, but they still face various obstacles in increasing their competitiveness, particularly in marketing. The problems identified in MSMEs selling Barangan Bananas in Suak Air Hitam Village, Pekaitan District, Rokan Hilir Regency include limited understanding and application of sharia marketing and low utilization of digital media in promotional activities. Unlike previous studies that focused on MSMEs in urban areas or businesses that have developed digitally, this study focuses on the application of sharia marketing in rural MSMEs. This study aims to analyze the role of sharia marketing in increasing the competitiveness of MSMEs from an Islamic economic perspective. The research motivation is based on the importance of strengthening MSME competitiveness through the application of sharia values ​​that are oriented not only towards profit but also towards business blessings. The study used a qualitative method with a descriptive approach. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The research results show that implementing the principles of honesty (shiddiq), trustworthiness, fairness, responsibility, and good service can increase consumer trust and loyalty, thereby strengthening business competitiveness. The policy implications of this research are the need for ongoing development and strengthening of Sharia-based digital marketing by local governments and related institutions to support the sustainability of MSMEs in rural areas.